PENERAPAN TEKNIK SPOTLIGHT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 1 GUNUNG TALANG KABUPATEN SOLOK - Siska, Rani Andela; Rismen, Sefna; Pratiwi, Merina (Pendidikan Matematika, 2013)
The research was due to the lack of studentsâ ability in understanding mathematic concept. The research aimed to find out whether studentsâ matematic understanding which were taught using spotlight technique better that of conventional learning. The design of the research was experimental research. The population was all students of grade IX SMPN 1 Gunung Talang. Based on the result of random sampling technique, grade IX4 was chosen as the experimental group, while the grade IX7 as the control group. The instruments used were essay test and understending concept indicators. The test consisted of eight questions, the reliability was 0,7695. The data was analyzed using one way t test whit MINITAB. Based on the analysis of hypothesis, it was obtained that the p-value = 0,003 was Â a. Thus, the hypotethesis was accepted. Therefore, it can be concluded that studentsâ math concept understanding using spotlight was better than that of conventional technique at grade IX students SMPN 1 Gunung Talang